Applications of Elidel for Lichen Plane (Texas Journal of Medical Science, 2022)
The problem of treatment of lichen planus and currently remains relevant. An important task of the topical application of medicinal compositions is to create an effective concentration in the focus of inflammation and maintain such a concentration for a long period of time. This study describes a method for the treatment of patients with lichen planus with the inclusion of sesoran ointment in standard therapy. A clinical study showed that with the use of the above preparation, regeneration of lichen planus was observed by the beginning of 2 weeks. The inclusion of Sesoran ointment in the treatment regimen allows accelerating epithelialization and tissue repair, and stabilizing the inflammatory process.